Subsurface delineation of doline features associated with Pleistocene clay-with-flints deposits in the Chilterns: Implications for British Palaeolithic archaeology. (December 2020) - Lim, Jonathan; Clark, James; Linares-Matás, Gonzalo
Highlights: The Chilterns landscape has a high potential for Palaeolithic archaeology. We used publicly-available geological and heritage datasets for predictive modeling. c.1270 probable subsurface features with Pleistocene CWF deposits were identified. This approach provides a valuable resource for informing heritage planning policy. Abstract: Palaeolithic research in the Chiltern Hills (southern England) is important for our understanding of the Pleistocene occupation of Britain, through its record of primary-context assemblages identified by Worthington G. Smith in the late 19th and early 20th centuries. The information available from these sites and surface findspots is limited by the context in which the assemblages were retrieved, but can inform attempts to locate further relevant sites within the region. These previous sites are all focused around doline features that may have acted as semi-permanent ponds or lakes that recurrently or occasionally attracted hominins. Therefore, the present study presents results of a desk-based geographical information system (GIS) analysis, using publicly available national geological datasets, aiming to identify and characterise probable subsurface doline features within the karstic landscape of the Chilterns, with a regional focus on Hyde Heath (Buckinghamshire). Rather than relying exclusively on surface findspot associations, we follow the Unified Palaeolithic Landscape Approach framework in relation to artefact release and preservation to refine which features would be most conducive to in situ primary preservation of hominin activity and behaviour. This also has implications for landscape management policy and preservation of archaeological sites in the region.